Differential Medication Attitudes to Antihypertensive and Mood Stabilizing Agents in response to an Automated Text-Messaging Adherence Enhancement Intervention - Klein, Peter (J Behav Cogn Ther, 2020)
OBJECTIVES: Individuals with serious mental illnesses such as bipolar disorder (BD) are at an increased risk for poor medication adherence compared to the general population. Individuals with BD also have high rates of chronic comorbid medical conditions like hypertension (HTN), diabetes, and cardiovascular disease. Cognitive-behavioral therapies often integrate strategies to improve medication adherence by targeting medication attitudes and self-efficacy, but the pathway toward behavior change needs further investigation. METHODS: This 3-month prospective, single-arm cohort study tested an automated SMS intervention entitled Individualized Texting for Adherence Building- Cardiovascular (iTAB-CV) in 38 participants with BD and HTN. The Tablets Routine Questionnaire (TRQ) measures the percentage of BD and HTN non-adherence over the past week and the past month. Attitudinal and habit measures including the Brief Illness Perception Questionnaire (Brief IPQ), the Medication Adherence Self-Efficacy Scale-Revised (MASES-R), the Self-Report Habit Index (SRHI), the Beliefs about Medicines Questionnaire (BMQ), and the Attitudes toward Mood Stabilizers Questionnaire (AMSQ) were given for BD and HTN medications. Correlational analyses were run to determine the associations between BD and HTN attitudinal and habit indices. Additionally, longitudinal analyses were conducted to determine if attitudes changed over time as a function of a 2-month mobile-health intervention. RESULTS: Illness attitudes towards BD were worse than towards HTN at the start of the study. Attitudes toward BD and towards mood-stabilizing drugs as well as antihypertensives improved following a mHealth intervention aimed at improving adherence. Furthermore, self-efficacy and habit strength for both BD and HTN drugs were correlated and were responsive to the intervention, with most of the change occurring after the first month of the intervention and not requiring the addition of the explicit reminders. CONCLUSION: Participants who received iTAB-CV showed improved attitudes towards BD and mood-stabilizing medication, and had an improvement in self-efficacy and habit strength towards taking both BD and HTN medications. Increased attention to mechanisms of change in mHealth interventions for adherence may facilitate impact. It should be noted that the methodology of the study limits drawing causal conclusions and suggests the need for a randomized control trial.